The Application and Modification of Goal-Based Evaluation as a Multifunctional Evaluation Method: A Systematic Review and Meta-Evaluation Study - Limiansi, Kintan; Tias Pratama , Anggi (Journal of Elementary School Education, 2023)
The Goal-based evaluation is an evaluation method introduced by Tyler as a pioneer in evaluating programs and policies in education. In practice, this method is also widely used by evaluators and researchers to evaluate programs in non-educational fields. Many publications report the results of evaluations from the 80s to the present, but have not made generalizations about these studies. This study aims to determine the application of goal-based evaluation as a generalized multifunctional evaluation method from various studies published online. Systematic reviews and meta-evaluations were carried out to investigate the characteristics of the evaluation research using the goal-based evaluation method, identify the steps of this method and discover the novelty of this method which can be adapted for subsequent applications. Data in the form of evaluation report articles were collected by searching online sources and selecting articles that met the criteria. Then each article is analyzed to find answers to the research objectives. The results of the study show that 1) the goal-based evaluation method can be used to evaluate various fields of study, 2) the steps of goal-based evaluation vary depending on the purpose of the evaluation, 3) modifications are carried out by the researcher by summarizing the evaluation steps, determining evaluators from various related fields, as well as determine program objectives at the outset in accordance with the parties related to the program. The application of goal-based evaluation and its modifications can be used as reference material for future evaluators in evaluating similar policies or programs as well as for researchers who will further develop this method.